A Literature Review and Exploratory Study of Existing Educational Mobile Applications in Turkey and Northern Cyprus - Bakshi, Rashmi; İlkan, Mustafa; Atalar, Erim (European University of Lefke, 2016)
[Abstract Not Available]
Keywords: User friendly, Usability, Context driven Smart phone applications